2019
DOI: 10.4103/jpbs.jpbs_173_18
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of acid-suppressing agents for stress ulcer prophylaxis in non-intensive care unit setting in Saudi Arabia

Abstract: Objective: To investigate the appropriateness of acid-suppressive therapy (AST) for stress ulcer prophylaxis (SUP) in noncritically ill hospitalized patients. Materials and Methods: A prospective, observational study with 384 subjects was conducted between October and December 2017 in the emergency and internal medicine departments. The Herzig clinical risk scoring system and the guidelines of the American Society of Health-System Pharmacists guidelines were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…4,5,23 Also, our rate is comparable to previously reported numbers in Saudi Arabia. 6,7 A prospective study conducted in emergency and internal medicine departments in Saudi Arabia showed that 59.5% of patients received omeprazole using an inappropriate route and 1.4% of patients received an improper dose of omeprazole, while 42.9% of patients received an inappropriate frequency of ranitidine. 6 In contrast, we found that 17.3% of patients were prescribed an inappropriate dose of AST, and 23% of patients received AST using an inappropriate route.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,23 Also, our rate is comparable to previously reported numbers in Saudi Arabia. 6,7 A prospective study conducted in emergency and internal medicine departments in Saudi Arabia showed that 59.5% of patients received omeprazole using an inappropriate route and 1.4% of patients received an improper dose of omeprazole, while 42.9% of patients received an inappropriate frequency of ranitidine. 6 In contrast, we found that 17.3% of patients were prescribed an inappropriate dose of AST, and 23% of patients received AST using an inappropriate route.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In Saudi Arabia, the reported incidences of inappropriate AST use in medical wards was even higher, ranging from 59.5% to 71.1%, while PPIs were the first choice among prescribers. 7,8 Even though there are no non-ICU specific guidelines for SUP for hospitalized patients, many prescribers follow the general guidelines that can be used whether patients are hospitalized or not. These guidelines include recommendations from the American College of Cardiology (ACC/AHA) for all patients using two or more antithrombotic agents 1,9,10 and the American College of Gastroenterology (ACG) for the prevention of nonsteroidal anti-inflammatory drug (NSAID)-related ulcer complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient population is defined as patients admitted to an ICU with coagulopathy, multiple traumas, >48 hours of mechanical ventilation, gastrointestinal bleeding (GIB) within the past year, sepsis, hepatic or renal transplant, > one week in the ICU, occult GIB for >6 days, >250 mg of steroid therapy daily, to name a few risk factors [10]. However, many studies have highlighted that the main risk factors for significant stress ulcer bleeding are mechanical ventilation for over 48 hours and coagulopathies, including platelets less than 50x109/L, international normalized ratio (INR) over 1.5, or partial thromboplastin time (PTT) over two times the control [5,[11][12][13][14][15]. Potential additional conditions associated with stress ulcers are a previous history of peptic ulcer disease, gastroesophageal reflux disease, chronic nonsteroidal anti-inflammatory drug use, Zollinger-Ellison syndrome, or brain or spinal cord injury [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used drugs for SUP in critically ill patients are proton pump inhibitors (PPIs) followed by histamine-2-receptor antagonists (H2RAs) ( Barletta et al, 2014 , Clarke et al, 2022 , Song et al, 2021 ). PPIs are the most prescribed anti-ulcer drugs (AUD) in Saudi Arabia and range from 87% to 94.5% ( Korayem et al, 2021 , Malhis et al, 2019 ). PPIs have greater benefits in reducing GI bleeding which was shown in several meta -analysis studies ( Alhazzani et al, 2018 , Wang et al, 2020 , Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%